Parantipathes pluma Opresko & Molodtsova 2021, n. sp. - Opresko, Dennis M.; Molodtsova, Tina N. (Zenodo, 2021)
Parantipathes pluma n. sp. (Figs 6–8) urn:lsid:zoobank.org:act: 7E0195DB-65A4-4DD9-9320-C013B125012A Parantipathes sp. Brugler et al . 2013: fig. 7A, 7D. Material examined. Holotype: USNM 1093058 (SEM stub 503), N. Pacific, central Aleutian Islands, S. of Amlia Island, ROV Jason II, Dive 95 (Field Identification Number: J 2095-2-7-4), 51.8116°N, 173.8328°W, 843 m, coll. R. Stone, 25 July 2004 (specimen dry). Paratype : USNM 1498742 (SEM stub 510), N. Pacific, Bering Sea, Zhemchug Canyon, F / V Cape Flattery , 58.5395°N, 175.0640°W, 977 m, coll. J. Hoff, 10 Jul 2016. Other Material : USNM 1093061, N. Pacific, central Aleutian Islands, Bobrof Island Pass, ROV Jason II, Dive 106 (Field Identification Number: J 2106-7-1), 51.8924°N, 177.2863°W, 936 m, coll. R. Stone, 7 Aug 2004; USNM 1482130, N. Pacific, central Aleutian Islands, SW of Adak Island, F/ V Ocean Olympic , 51.5270°N, 177.0170°W, 329 m, coll. G. Nightengale, Oct 2004. Diagnosis . Tall colonies, monopodial, unbranched or sparsely branched to the second order. Stem and branches pinnulate. Pinnules mostly simple, up to 13 cm long, arranged bilaterally along the stem, and, in varying degrees of regularity within and between colonies, with two to three rows on each side of axis, and in alternating semispiral groups typically consisting of two or three, and very rarely four pinnules. Pinnular density very variable depending on specimen, location on corallum, number of pinnules per group, and spacing of pinnules within and between groups; commonly 13–16 total per cm, but ranging from about 10 to 19 per cm. Pinnular spines usually simple (rarely with apical lobes), smooth, perpendicular to the axis, with 4–5 spines per mm; polypar spines mostly 0.06–0.08 mm tall (maximum about 0.09 mm); abpolypar spines 0.04–0.06 mm. Polyps on pinnules estimated to be 2.8–3.2 mm in transverse diameter with 2.5–3 polyps per cm. Description of holotype. Holotype (USNM 1093058, Fig. 6A) monopodial, without branches, but pinnulate with simple pinnules in multiple rows along the ...